Produtividade e qualidade do repolho adubado com nitrogênio e boro em ambiente protegido no Amazonas - (:unkn) unknown (Universidade Federal do Amazonas, 2015)
The balanced fertilization with N and B, can change the nutrition and characteristics productive of the cabbage. By applying combination of N and B, it aimed the best combination of N and B for cultivated cabbage fertilization in typical Amazon soil. The experiment was conducted in Green House on the campus of the Federal University of Amazonas, from May to September 2014. The material used as a substrate was an Oxisoil, clayey, typical of the Amazon region. Treatments were a combination of 5 (five) doses of N (0; 150; 200; 250, and 300 kg ha-1) as urea with 4 (four) doses of B (0; 2; 4 and 8 kg ha-1) in form of boric acid and 4 (four) replications, arranged in experimental design of randomized block, and analysis factorial 5 x 4 making 20 combinations of N and B. The fertilization of plants were applied in soil 20% of all doses of N; 200 kg P2O5 ha-1; 20% of 150 kg of K2O ha-1; 1,5 kg CuSO4 ha-1; 0,15 kg MoO3 ha-1; 3,66 kg MnSO4 ha-1 and the doses of B. In fertilization of coverage were applied in soil the remainder of K2O and the doses of N splitted (20, 30 and 30 % the 20, 40 e 60 DAT). At harvest were evaluated the productive characteristics of plants (height and diameter of the shoot; number of outer leaves; fresh and dry outer leaves; dry root mass), the quality and (fresh and dry; height; diameter; weight; compactness of head and the number of outer leaves), the absorption of the B and N by cabbage and productivity when certain treatments showed compact cabbages with edge of the sheet of head, starting his detachment at. The fertilization with N and B positively influenced the components of production, being the essential N to obtain satisfactory production results, therefore together with B increases the mass of dry matter in the head, dry mass and inner sheets and productivity. The conditions under which the experiment was conducted, in its first approach was 230 kg N ha-1 and 1,12 kg B ha-1.
Keywords: Adubação química; Nutrição de plantas; Chemical fertilization; Plant nutrition; CIÊNCIAS AGRÁRIAS: AGRONOMIA